The Irish market services sector: an econometric investigation - Bradley, John; Fitzgerald, John; Kearney, Ida (Economic & Social Studies, 1991)
Using new time series data a structural econometric model of a three way disaggregation of the market services sector is constructed. The elasticities of demand for the factors of production (capital and labour) in two of the sub-sectors were found to be moderate in size with elasticities proving rather small in transport and communications. While prices, in the long run, are set as a mark-up on costs, in two of the sub-sectors short-term pricing decisions were found to be significantly affected by capacity utilisation.
Keywords: market services; Ireland; econometrics